Consumers Preference towards Various Brands of Noodles in Kathmandu Valley (Sotang, Yearly Peer Reviewed Journal, 2023)
This topic of study aims at finding out whether the consumers’ expectations of matched their satisfaction level on the basis of quality products provided by Noodles companies (i.e. RARA, WAI-WAI, MAYOS, YUM YUM and 2PM). So, the research is to study the preference of the consumers and their satisfaction level. A survey design with a questionnaire tool was used for collecting data with a view to remaining competitive leading position and for businesses to grow, product quality and consumers’ preference are key ingredients. These two paradigms are rather different concepts; however, they are closely correlated. The purpose of this study was to describe how consumers perceive product quality whether they are satisfied with product/Noodles offered by the stated/sample companies. The thrust of this study was to compose an assessment of product quality and consumer satisfaction of the companies. The questionnaire was distributed using a convenience sampling technique among 150 respondents in the Kathmandu Valley. From the analysis, it was found that the overall product quality offered by the companies WAI-WAI and RARA was relatively higher than others. Further, the analysis proved that the dependency of consumer satisfaction on the quality of product and value for money had high positive correlation. As such, it appears that the most of the Noodles companies need to be very much concerned with the satisfaction of consumers by offering quality products with reasonable prices. The researcher makes a few recommendations based on the findings of the study. First of all, the management of the companies should pay attention to improve the product quality and other factors which may lead to consumer satisfaction thereby improving its performance and the overall brand image and profitability of the companies.